Archival Knowledge, Indigenous Knowledge, and Challenges in Collection Management: An Australian Case Study - Toner, Peter (MUSICultures, 2025)
This article examines the Daymbalipu Mununggurr Collection of Yolngu music, made in northern Australia in the late 1970s and early 1980s and lodged at the Australian Institute of Aboriginal and Torres Strait Islander Studies (AIATSIS), as an example of the intersection of partially incommensurable systems of knowledge. When Indigenous recordists and collectors do not share with archives and archivists fundamental premises about the nature of sound recordings and their associated management practices, this can result in diminished or problematic access to their collections but also can suggest new possibilities for archive-community co-management.